Peran Faktor Domestik Jepang dalam Kebijakan Investasi Proyek PLTU Batang - Faiz Balya Marwan (Universitas Diponegoro, 2020)
Japan is one country that is consistent with green policies both in domestic and foreign policy through the Chonaikai movement and the green industry. The policy cannot be separated from the role of the development of Japan’s green groups that emerged since the world oil crisis of the 1970s. However, in 2011 there was a policy inconsistency marked by an upward trend in Japanese investment in developing coal-based projects. The biggest investment is in Indonesia in the development of the Batang PLTU. Batang PLTU is a national strategic project as a result of the 2005 Infrastructure Summit which is inconsistent with green politics in Japan’s foreign policy. This article analyzes Japan’s supports the Batang PLTU project using Lovell’s foreign policy process approach. This article argues that Japan’s decision to invest in the Batang PLTU project cannot be separated from the existence of information input in the form of domestic demand, domestic opinion, domestic interests, and Japanese domestic needs. This is inseparable from the financial and political power of business groups that are able to indirect lobbying and direct lobbying.